Inclinations of Saudi Arabian and Malaysian Students Towards Entrepreneurship - Parveen, Musrrat; Kassim, Norizan M.; Zain, Mohammed (Prabandhan: Indian Journal of Management, 2018)
This study investigated the cognitive factors (such as social norms, attitudes, and perceived behaviors) and other factors (such as risk taking, innovation, and perceived risk) that led to entrepreneurial intention amongst university students in Malaysia and Saudi Arabia. Data were collected via a questionnaire survey involving 416 students in these two countries. Overall, the results clearly showed significant differences between the two groups of respondents in all the entrepreneurship intention variables examined in this study. The results suggested that business knowledge played a very important role in determining entrepreneurial intention amongst the students of both countries. As for the differences, amongst the Malaysian students, perceived risk of doing business had medium significant effect on intention, followed by innovation and business knowledge ; whereas, amongst the Saudi Arabian students, business attractiveness was found to have very strong significant effects on intention, followed by readiness to do business and business knowledge. Some practical implications of the findings are also suggested.